Condutos poliméricos microestruturados longitudinalmente para o reparo do nervo periférico - Garcez, Giovanna Ramos (2015)
Peripheral nerve injuries are a common clinical problem and the development of new approaches to assist in its repair has been shown to be a growth area. The use of microstructured channels has been investigated, in order to promote cell growth guided by assisting in the damaged tissue recovery. Biocompatible and biodegradable materials can be applied for the construction of these devices by eliminating the need for a second procedure to remove the implant. This work proposes the preparation of microstructured film along channels aligned with polydimethylsiloxane (PDMS) and blends of polycaprolactone (PCL) and poly (lacticco- glycolic acid) (PLGA) for potential application in peripheral nerve regeneration. PDMS films were prepared by the method of mixing the solution with oligomers based curing agent. Blends of PCL (Mn = 80.00) and PLGA (85:15) with different ratios of PCL / PLGA (100/0, 90/10, 80/20 and 70/30) were prepared by the solvent evaporation method. The mold used to produce the films consisted of channels with different widths (5, 10, 15 and 20 μm) and constant height (25 μm). The materials were characterized by Scanning Electron Microscopy (SEM), Infrared Spectroscopy Fourier Transform (ATR / FT-IR), thermal gravimetric analysis (TGA), Atomic Force Microscopy (AFM). To evaluate the degradation time of the films was carried out in vitro degradation test of PCL blends and PCL / PLGA observing weight loss 0.4 to 9.9% until 90 days testing. It was found that the addition of the PLGA PCL is an effective way to control the degradation rate of the blend and there is no significant difference in the degradation of flat and microstructured films.